Felix in the underworld - Mortimer, John Clifford 1923-2009 (Viking, 1997)
In England, a woman sues a writer for support, naming him father of her 11-year-old son. When the woman is killed the writer is a suspect and goes into hiding among the homeless, but is caught. Thankfully, there is his publicist, whom he has always been nice to, and she might clear his name.
Keywords: Authors -- Fiction; Detective and mystery stories.; London (England) -- Fiction; Detective and mystery stories